Sharon and my mother-in-law Ramallah diaries - Amiry, Suad (Granta Books, 2005)
Surprisingly funny and refreshingly different from any other writings on the Palestinian-Israeli conflict, Sharon and My Mother in Law describes Suad Amiry's experience of living on the West Bank from the early eighties to the present. Tells about the life and neighbourhood gossip, family history and the struggle to live a normal life.